Risk Factors for Narcotic Use in Street Children: A Cross-Sectional Analysis From a Low-Middle-Income Country - Anum Waheed MBBS MSPH; Mariyam Sarfraz MSc, PhD; Amna Mahfooz MBA, MSPH; Tahira Reza MBBS, MSc; Faran Emmanuel MBBS, MSc (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
Worldwide, indulgence in high-risk behaviors such as substance abuse is on the rise in street children. Though substance abuse among street children has been investigated and reported in Pakistan, few studies have explored the relationship between narcotic use and its associated factors. This study was conducted to determine factors associated with narcotic use among street children in Islamabad Capital Territory. An analytical cross-sectional survey of a probability-based sample of 443 (males) street children aged 12 to 18 years, was conducted in Islamabad in March 2022. Using self-reported measures, the relationship between narcotic use and associated factors was determined using multivariate regression analysis. Out of 443 street children, with a mean age of 16.3 ± 1.6 years, 244 (55%) were between 17 and 18 years old. 119 (26.9%) worked as garbage collectors and 76 (17.2%) worked as car washers. The most common substance used was cigarettes in 285 (64.3%), naswaar in 172 (38.8%), hashish in 144 (32.5%), and alcohol in 63 (14.2%) street children. There were 164 (37%) street children who admitted having used narcotics (hashish, heroin, and bhang). On multivariate analysis, age > 16 years (OR: 2.3), sleeping on the streets (OR: 2.4), higher monthly income > Rs.18,000 (OR: 1.6), use of drugs by friends (OR: 5), and involvement in the selling of drugs (OR: 10.3) were independently associated with narcotic use. Substance abuse is a concerning trend among street children in Islamabad. When certain high-risk factors are present, these children are prone to narcotic use.